The Influence of Digital Literacy on Employee Performance with Work Ethic as a Moderating Variable - Murni Yanto (Yayasan Inovasi Kemajuan Intelektual, 2022)
This research is a quantitative research with an explanatory approach, namely an approach that has a strong relationship with previous studies, such as siblings, to create, modify, and prove the hypothesis in this article. The data used in this study is primary data that the researcher obtained from an online questionnaire distributed to two hundred and eighty-five employees of “Mitra Sepuluh” Company, spread throughout Indonesia. The data that the researcher obtained was analyzed using the smart PLS 4.0 analysis tool. The conclusion in this article shows that the Digital Literacy variable has a positive relationship direction and a significant influence on Employee Performance in the first hypothesis. This is because the P-values in this article are positive and below the 0.05 significance level, namely 0.016. These results mean that the better digital literacy possessed by an employee can make employees smarter, make it easier for them to complete tasks for the company, and ultimately improve employee performance. In the next hypothesis, the Work Ethic variable can also moderate the influence of the Digital Literacy variable on Employee Performance because the same thing is that the P-Values are positive and below the 0.05 significance level, namely 0.000, more significant than the direct test of 0.000. Thus, it can be concluded that the first and second hypotheses in this article can be accepted and proven